Conscious Teaching: Strengthening teacher well-being and supporting sustainable classroom management - Wilhelm, Jona (My University, 2025)
Teachers in Swedish schools are increasingly experiencing high levels of stress and professional strain, contributing to a growing number choosing to leave the profession. This trend has significant consequences for the learning environment and student outcomes. The aim of this thesis is to explore how mindfulness-based techniques can support teacher well-being and contribute to improved classroom management. The research was conducted through an ethnographic field study in Koh Phangan, Thailand, where the author participated in a leadership retreat led by educator and leadership expert Rick Smith. In addition, a literature review was performed to identify relevant theoretical and practical perspectives. Based on insights from the field study, interviews, and literature, a mindfulness toolbox was developed and tested in a small-scale intervention involving three in-service teachers working in challenging school environments. The results of the intervention indicate that mindfulness practices can increase emotional awareness, enhance presence, and improve relational dynamics in the classroom. Teachers reported greater calmness, patience, and self-reflection in their professional practice. Although mindfulness is not widely implemented in Swedish schools, the findings suggest that it may offer a low-cost and accessible approach to strengthening teacher resilience and pedagogical effectiveness. As a practical outcome of this research, the toolbox was translated into Swedish and adapted into a card deck format to support teacher-led reflection and workshop activities. This thesis contributes to the growing body of research on mindfulness in education and highlights its potential role in addressing the well-being challenges currently facing the Swedish school system.
Keywords: Teacher well-being, Mindfulness-based interventions (MBIs), Classroom management, Emotional regulation, Inner authority, Ethnographic research, Micro-phenomenological self-inquiry